Test generation for graphical user interfaces based on symbolic execution - Ganov, Svetoslav R; Killmar, Chip; Khurshid, Sarfraz; Perry, Dewayne E (International Conference on Software Engineering 2008, 2008)
While Graphical User Interfaces (GUIs) have become ubiquitous, testing them remains largely ad-hoc. Since the state of a GUI is defined by a sequence of events on the GUI's widgets, a test input for a GUI is such an event sequence. Due to the combinatorial nature of the sequences, testing a GUI thoroughly is problematic and time-consuming. Moreover, the wide range of possible values for certain GUI widgets, such as a textbox, compounds the problem.